An Improved Design Procedure for LCC Resonant Filter of Dimmable Electronic Ballasts for Fluorescent Lamps, Based on Lamp Model - Wakabayashi, Fabio Toshiaki [UNESP]; Canesin, Carlos Alberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2003)
This paper presents an improved design methodology for determining the parameters used in the classical Series-Parallel Loaded Resonant (SPLR) filter employed in the switching frequency controlled dimmable electronic ballasts. According to the analysis developed in this paper, it is possible to evaluate some characteristics of the resonant filter during the dimming process, such as: range of switching frequency, phase shift and rms value of the current drained by the resonant filter + fluorescent lamp set.
Keywords: Series parallel loaded resonant (SPLR) filters; Switching frequency; Ballasts (lamp); Dimming (lamps); Electric currents; Fluorescent lamps; Phase shift; Product design; Switching; Bandpass filters